2013
DOI: 10.1159/000348385
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Inflammation-Based Predictors of Tumor Response to Neoadjuvant Chemoradiotherapy for Locally Advanced Rectal Cancer

Abstract: Background: The ability of pretreatment laboratory markers of acute-phase inflammatory reactions like serum albumin level (SAL), hemoglobin (Hb), and absolute blood cell counts to predict complete pathological response (CPR) to neoadjuvant chemoradiotherapy (NACRT) in patients with locally advanced rectal cancer (LARC) has not yet been fully studied. Methods: We retrospectively examined the relation between SAL, Hb and absolute blood cell counts, and CPR rates in 140 LARC patients treated with NACRT. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 35 publications
6
48
1
3
Order By: Relevance
“…Krauthamer et al [22] showed that high NLR (>5.0) was independently associated with pCR in multivariate analysis. Kitayama et al [23] reported that the percentage of lymphocytes in WBC were independent predictors of pCR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Krauthamer et al [22] showed that high NLR (>5.0) was independently associated with pCR in multivariate analysis. Kitayama et al [23] reported that the percentage of lymphocytes in WBC were independent predictors of pCR.…”
Section: Discussionmentioning
confidence: 99%
“…They chose 5.0 as the NLR cut-off value, but they did not document the proportion of high and low NLR patients. However, there is no consensus about an NLR cut-off value, and the cutoff values that were used in previous reports targeting rectal cancer patients with NACRT were 2.8, 3.0, and 5.0 [18][19][20][21][22] . Shen et al [18] used both cut-off values of 2.8 and 5.0, and an NLR of ≥ 5.0 was also independently associated with worse OS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in our study, the lymphocyte counts and ratios were not significantly different when the good and poor response groups were compared. Krauthamer et al [19] studied predictors of tumor response to preoperative CRT in rectal cancer and determined that serum albumin (>3.5 mg/dl) and NLR (<5) were predictors for complete pathologic response in clinical stage III (n = 71) patients but not in clinical stage II patients. They explained that no association between NLR and clinical stage II disease may be due to small study samples.…”
Section: Discussionmentioning
confidence: 99%